Frequency of Incidental Carcinoma Gall Bladder in Laparoscopic Cholecystectomy - Jahangir Sarwar Khan , Hasan Ali ,Iram Hassan , Mohammed Mussadiq Khan , Muhammed Iqbal (Journal of Rawalpindi Medical College, 2013)
Background: To determine the frequency of incidental carcinoma gallbladder in cases of laparoscopic cholecystectomy.. Methods: In this descriptive study all the patients presenting with diagnosis of cholelithiasis were included. They were operated by laparoscopic cholecystectomy and histopathologic studies were done to detect any evidence of malignancy. Results: Out of 500 cases of laparoscopic cholecystectomies done for cholelithiasis over a period of 5 years, only one case of adenocarcinoma (0.2%)was detected. The tumour was limited to mucosa. There was no evidence of involvement of lymph nodes or metastasis. Conclusions: Despite the common notion that carcinoma gallbladder is common in our region. present study clearly showed a low frequency of incidental carcinoma gallbladder in patients undergoing laparoscopic cholecystectomy.